Acquisition of Tone Sandhis by English Speaking Learners of Chinese - Wenhua Jin (Journal of the National Council of Less Commonly Taught Languages, 2019)
This study examines the acquisition of five Chinese tone sandhis, including Yi, Bu, T2, Half-T3, and T3 Sandhis by English speaking learners of Chinese. Fifty-three college students from different levels of Chinese classes participated in this study. Investigation results show different acquisition patterns for the various sandhi processes and learner levels, revealing thereby multiple factors at play in L2 learners’ acquisition of the tone sandhis: the instruction factor, phonetic motivation, learning effect, inherent intra-lingual factor, and interference from English intonation. This study provides valuable implications for L2 Chinese pedagogy as well as Second Language Acquisition in general and also presents new evidence for the understanding of the long debated nature of Chinese Tone 3 from the perspective of L2 Chinese acquisition.